Training requirements for the administration of intravenous contrast media by radiographers: Radiologists’ perspective - G Koch; L Swindon; J Pillay (South African Medical Association, 2017)
Background. The administration of intravenous contrast media (IVCM) is one of the key areas currently under investigation for inclusion in the South African (SA) radiographers’ scope of practice. However, for the radiographers to legally administer IVCM, training guidelines must first be identified, developed and accredited by the Health Professions Council of SA.Objective. To investigate the radiologists’ perspective of the knowledge, skills and medicolegal training required of radiographers for the administration of IVCM to provide input for the development of national training guidelines.Methods. A quantitative, cross-sectional research study using an online survey, administered by SurveyMonkey, was conducted. The target population included all radiologists residing and practising in the province of KwaZulu-Natal, SA.Results. Fifty-nine participants (60.8%) completed the online survey. Twelve were excluded owing to incomplete surveys, resulting in a final response rate of 48.5% (n=47). The study revealed that various theoretical, clinical/practical and medicolegal study units should be included in the training, i.e. the study of the pharmacology of contrast media, practical training on cardiopulmonary resuscitation and basic life support, as well as the rights and responsibilities of a healthcare professional. In addition, both theory and practical/clinical assessments need to be included.Conclusion. Key data have been provided for the development of national training guidelines for radiographers to administer IVCM, based on scientific evidence that is relevant to the SA context. The study may be of value to other related health professions where scopes of practice are expanded through transforming the education and training curricula.